Assessment of agricultural sustainability performance in Dali Prefecture, China using the DPSIR Model - Yishan Chen; Harison Kiplagat Kipkulei; Zhiqiang Xie; Stefan Sieber (International Journal of Agricultural Sustainability)
Urbanization and ecological efforts in China have significantly altered agricultural land use affecting both the quantity and quality of arable land. There has been a rise in the use of energy, fertilizers, pesticides, and plastic films to enhance production. However, these unsustainable farming practices have led to higher greenhouse gas emissions and the risk of agricultural non-point source pollution. The Yunnan Province government aims for sustainable agriculture to enhance product quality and China’s green farming. Yunnan’s proximity to the Yangtze, Lancang, and Yuan Rivers makes agriculture vital for the downstream livelihoods and biodiversity. This study explored factors affecting agriculture in Dali Prefecture, Yunnan Province. The study proposed a comprehensive system of 33 indexes to assess agricultural sustainability performance using the Driver-Pressure-State-Impact-Response framework. It employed a composite weight method combining the Analytic Hierarchy Process and Entropy Weight methods. The assessment showed that all counties except Dali City scored a performance index below 0.5. Furthermore, the “Response” indicator was found to be crucial in advancing agricultural sustainability. Conversely, factors leading to unsustainable changes, like “Driver” were less significant. The study reveals that data statistics prioritize indexes related to land resources while experts emphasize indexes linked to socioeconomic status when assessing agricultural sustainability.